2016
DOI: 10.1007/s10237-016-0771-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue growth constrained by extracellular matrix drives invagination during optic cup morphogenesis

Abstract: In the early embryo, the eyes form initially as relatively spherical optic vesicles (OVs) that protrude from both sides of the brain tube. Each OV grows until it contacts and adheres to the overlying surface ectoderm (SE) via an extracellular matrix (ECM) that is secreted by the SE and OV. The OV and SE then thicken and bend inward (invaginate) to create the optic cup (OC) and lens vesicle, respectively. While constriction of cell apices likely plays a role in SE invagination, the mechanisms that drive OV inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 54 publications
7
61
1
Order By: Relevance
“…While the majority of extracellular signaling plays positive roles in lens cell formation, the repressive mechanisms seem to be underepresented (Table 1), and various cross-talks between individual pathways remain poorly understood [131, 190, 236]. Other levels of unresolved complexities relate to the contradictory findings that optic cup formation requires ectoderm-derived signals [137], anopthalmia is caused by various mutations of genes either in the ectoderm or optic vesicle [3, 51, 54, 79, 82, 83, 237], and that optic cup formation proceeds without any rudimentary lens in retinal organoid cultures [125, 238]. These and other outstanding questions previously discussed will be resolved in the upcoming years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of extracellular signaling plays positive roles in lens cell formation, the repressive mechanisms seem to be underepresented (Table 1), and various cross-talks between individual pathways remain poorly understood [131, 190, 236]. Other levels of unresolved complexities relate to the contradictory findings that optic cup formation requires ectoderm-derived signals [137], anopthalmia is caused by various mutations of genes either in the ectoderm or optic vesicle [3, 51, 54, 79, 82, 83, 237], and that optic cup formation proceeds without any rudimentary lens in retinal organoid cultures [125, 238]. These and other outstanding questions previously discussed will be resolved in the upcoming years.…”
Section: Discussionmentioning
confidence: 99%
“…This contact is established by the constraining effects of ECM [123] and the formation of F-actin-rich basal temporal filopodia acting as physical tethers [124]. This model was further extended by findings which showed that the ECM causes lens cells to thicken locally in order to facilitate subsequent invagination [99, 125], a process primarily driven by both apical constriction to produce wedge-shaped cells [122, 126] and by BMP signaling [127]. In the invaginating lens placode, the cells near the lens pit circumferentially contract the adherens junctional complexes joining them together, and this actomyosin cytoskeleton remodeling requires RhoA small GTPase, Rho-kinase (Rock), PDZ domain-containing protein Shroom3, and p120-catenin δ1 [122, 126].…”
Section: Lens Morphogenesis and Gene Regulatory Networkmentioning
confidence: 99%
“…intestinal looping | buckling | biomechanics | Bmp | morphogenesis D ifferential growth represents one of the core physical mechanisms driving morphogenesis throughout the vertebrate embryo (1)(2)(3)(4)(5)(6)(7)(8)(9). Investigations into the mechanics of differential growth have often illustrated key physical parameters (e.g., tissue stiffness, growth rates, and initial geometry) that determine the resultant tissue shape.…”
mentioning
confidence: 99%
“…This characteristic behavior of multicellular tissue would be modeled as a change in stress-free configuration. The second is a mechanical constraint, such as extracellular matrix surrounding a growing tissue, that determines the direction of invagination (Huang et al 2011;Oltean et al 2016). Further analysis is required to investigate the effects of mechanical constraints modeled as boundary conditions on tissue deformation.…”
Section: Discussionmentioning
confidence: 99%